2010
DOI: 10.5393/jamch.2010.35.4.395
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Trust in Healthcare System and Health Examination Participation

Abstract: Objectives: This study was conducted to investigate the relationship between vertical trust in the healthcare system and participation in routine health examinations. Method: Data from the 2008 Pusan Health Survey were analyzed for this study. Multiple logistic regression analyses were performed to investigate the influence of possible confounders (sex, age, education, monthly mean household income, horizontal trust) on participation in routine health examinations according to trust in the healthcare system. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…As a result, people with a strong sense of community more actively participate in health screenings, which suggests that individuals with positive views of their communities make more significant efforts to promote their own health [ 29 ]. The OR at the regional level was not higher than it was at the individual and household levels in this study, which was consistent with previous studies that found the influence of the regional level to be insignificant [ 17 , 18 , 32 ]. Lee and Kim [ 33 ] reported that the OR for the proportional social welfare budget, which was used as a regional level variable, was 0.991 (95% CI, 0.983 to 0.998), and it was 0.980 (95% CI, 0.970 to 0.996) in Kim[ 21 ]’s study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As a result, people with a strong sense of community more actively participate in health screenings, which suggests that individuals with positive views of their communities make more significant efforts to promote their own health [ 29 ]. The OR at the regional level was not higher than it was at the individual and household levels in this study, which was consistent with previous studies that found the influence of the regional level to be insignificant [ 17 , 18 , 32 ]. Lee and Kim [ 33 ] reported that the OR for the proportional social welfare budget, which was used as a regional level variable, was 0.991 (95% CI, 0.983 to 0.998), and it was 0.980 (95% CI, 0.970 to 0.996) in Kim[ 21 ]’s study.…”
Section: Discussionsupporting
confidence: 92%
“…Studies that conducted multi-level analyses of health-related behaviors found that financial independence, the number of fast-food restaurants per 1000 residents, the crude divorce rate, the number of vehicle registrations, and the adjusted death rate had statistically significant effects on obesity [ 16 ], and that changes in the number of individuals with drinking problems could be explained by the number of pubs and changes in the crude divorce rate in areas where drinkers resided [ 17 ]. One study that found that the health screening rate of people with high community trust was greater than that of those with low community trust [ 18 ] also found that participation in health screenings cannot be attributed solely to individual characteristics. The study by Jeong et al [ 19 ] that analyzed regional variables related to health level and health behaviors provides evidence in favor of establishing health policies tailored to the characteristics of specific regions.…”
Section: Introductionmentioning
confidence: 99%